Monga: anatomy of a movie blockbuster made in Taiwan - Wang, Siqi (2021)
In 2008, the box office success in Taiwan of Cape No. 7 (Haijiao Qihao, dir. Wei Desheng, 2008), alongside several other movies produced in the country, revealed the potential vibrancy of the Taiwanese film market as well as the appetite for local stories among Taiwanese audiences. Niu Chengze and Li Lie, director and producer respectively of the subsequent Monga (Meng Xia, dir. Niu Chengze, 2010), seized this market opportunity to design a business plan to produce what became a made-in-Taiwan blockbuster. Monga is a very significant film in the history of Taiwanese cinema. Upon its release, it broke several records, including the highest-grossing opening for a Taiwanese film in Taiwan, the quickest time to earn 100 million New Taiwan dollars, opening launch on the greatest number of screens, and the first Taiwanese film to be released during the important spring festival holiday season for twenty years. This thesis poses the following research question: what does Monga’s popularity reveal about film production, distribution, promotion and reception in Taiwan, in Greater China and for film industries and culture overall? To address this question, the study adopts a multidimensional approach to investigate the film’s production, distribution, promotion, and reception. Because of this intention to provide a full analysis of the multifaceted complexity of the Taiwanese blockbuster as a cultural product, the thesis uses a mixed research methodology. Its bilingual (English/Chinese) cultural-industrial approach, therefore, encompasses interviews with relevant Taiwanese film workers, economic and industrial analysis, textual analysis of media coverage, film consumption data from media platforms, and consideration of the project’s relationship to scholarly debates on contemporary Taiwanese cinema. The project’s findings demonstrate that Monga marked a new stage of evolution for contemporary Taiwanese cinema and the Taiwanese blockbuster. Using a business plan encompassing governmental funding, the support of Hollywood distributor Warner Bros., and a strategic marketing campaign, the film was a box office triumph. The project also functioned as a stepping-stone for Taiwanese filmmakers to attract more sizeable investments to help them break into the booming film market in mainland China, as Monga’s distribution there through informal media platforms aided the production of Niu’s next project, Love (Ai, 2012), a coproduction facilitated by a major investment by Huayi Brothers.